Representations about the teaching practice in the initial education of Geography teachers (Olhar de Professor, 2011)
This article presents the results of an investigation carried out with students of the 4th year of the teaching degree in Geography at the State University of Ponta Grossa (UEPG), Pr and teachers of basic education in 2007 and 2008. The research tried to identify the formative possibilities that the teaching practice experience provided to the initial education of Geography students. This identification is based on students´ and teachers´ conceptions about the importance of the teaching practice to the future profession. The aim of the study is to reflect on the construction process and teaching professionalization development during the teaching practice in basic education schools. In this article, students´ evaluation of the teaching practice experience and of the undergraduate course are presented. The opinions of basic education teachers’ about the importance of the activities are also analyze.
Keywords: Geography. Teaching practice. Initial education.